Kajian Yuridis Tanggung Jawab Sosial dan Lingkungan Perusahaan di Kota Manado - Gerungan, Carlo Aldrin; Pondaag, Audi Herli; Gerungan, Mario A. (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The aim of the research is to take an inventory of regional regulations regarding the implementation of Corporate Social and Environmental Responsibility (TJSLP) in Manado City. The results of this normative juridical research show the TJSLP concept in Manado City. This normative juridical examination is important to measure the company's contribution to sustainable development and the welfare of the people of Manado. Involvement of local governments in preparing regulations to create a sustainable and responsible business environment. Rules regarding the implementation of corporate social and environmental responsibility are carried out through several specific rules and policies that have been established by the Manado City Government.